Diagnostic challenges and treatment breakthroughs in Malassezia restricta-induced meningoencephalitis: a real-world analysis of early mNGS applications - Wang, Jian; Tao, Lin (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundMalassezia restricta is a lipid-dependent yeast species that commonly colonizes human and warm-blooded animal skin as an opportunistic pathogen. Although strongly associated with dermatological conditions like seborrheic dermatitis, central nervous system (CNS) infections caused by Malassezia restricta are remarkably rare. These infections typically present with nonspecific clinical features, leading to frequent diagnostic delays and misdiagnosis.MethodsWe performed a retrospective analysis of five definitive cases of Malassezia restricta-induced meningoencephalitis diagnosed at our institution. Comprehensive clinical evaluations included disease onset patterns, symptomatology, laboratory findings, neuroimaging features, therapeutic regimens, and patient outcomes.ResultsAll patients exhibited acute onset meningoencephalitis, with headache being the most common presentation symptom, and patients presenting with decreased consciousness showed rapid clinical deterioration. Brain magnetic resonance imaging (MRI) exhibits ring enhancement accompanied by ring diffusion restriction, plays a crucial role in early diagnosis. The cerebrospinal fluid (CSF) demonstrated markedly elevated intracranial pressure and a significant decrease in CSF glucose, vital laboratory markers of critical illness. Metagenomic next-generation sequencing (mNGS) of CSF confirmed Malassezia restricta infection in all cases, enabling prompt diagnosis. Early combination therapy with intravenous and intrathecal antifungal agents significantly improved survival outcomes.ConclusionMalassezia restricta-associated meningoencephalitis represents an extremely rare and life-threatening CNS infectious disease. Since nonspecific early symptoms lead to diagnostic challenges, CSF usually shows a significant increase in intracranial pressure, and a significant decrease in CSF glucose levels may serve as a key laboratory biomarker. Brain MRI demonstrates multiple and diverse intracranial lesions, with ring enhancement accompanied by ring diffusion restriction potentially representing relatively specific imaging features. mNGS of CSF may prove valuable for early diagnosis. Standardized antifungal therapy, particularly early intrathecal administration, may be critical to reducing mortality.